Women Empowerment and Education: Exploring the Links Between Women's Empowerment, Education, and Social Issues in Modern India (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The status of women in India had been subject to several great changes and challenges over the led past few millennia. In times of yore, Indian women accustomed enjoy equal status with men. Many reformers and social workers protected the rights of women either due to the role of women within the society or their special character as described in Upanishads. But during the medieval period, the rights of women had declined in spite of arguments and support from many reformers. In modern India, women are holding high level positions in administration, corporate sector and politics. They held high positions like President of India, Prime Minister of India, Speaker of Loksabha, etc., in Indian Parliament. Despite these facts, women in modern India are exposed to numerous social problems and issues. In keeping with a global study conducted by Thomson Reuters, India is that the fourth most dangerous country within the world for women. During Vedic period it's noted that women enjoyed equal rights, sometimes better status than men. Women’s rights were curtailed and more protectionist attitude towards women prevailed during medieval period. Many restrictions and conditions were placed on women’s education, religious rights and privileges and on their social and political activities. India now has not only women doctors, engineers, judges and officials holding high ranks but also women political leaders who mold and shape the destiny of India. The women have the power to settle on and dictate in keeping with their ambitions, but the society and men are the matter to them. Here lies the matter of human valves and relationships. They merely don't require merely legal measures for equal rights, but sympathy and understanding both reception and within the place of labor. A cursory glance at the published literature brings home that present research subject has been studied by many scholars but with different angles and intensions. It should be noted that the main focus of above-mentioned studies is just too general and broad. There are hardly few studies which examined existence of women empowerment and education along with employment and income. Further, no study is accessible which studies the intra community differences. Hence, it had been thought of undertaking this research work on women empowerment and education.